SISTEM INFORMASI GEOGRAFIS PENYEBARAN LOKASI LEMBAGA BIMBINGAN BELAJAR DI KOTA PADANG BERBASIS ANDROID - Ganda Yoga Swara; Septi Jeni Ramadhan (ITP Press, 2017)
A tutoring center is an independent, non-formal education that server students to get an extra school hours. Currently, it’s become a necessity for students, especially for who wants to continue their higher degree of study. In padang, there are more than 50 tutoring center for high school level that spread in several districts. The increasing number of existing centers indirectly caused a trouble for communities difficult to remembering every location of all available tutoring centers, especially for the newcomers. In term of that, it necessary to build a system with geographic information system (GIS) for search tutoring center location at padang based on android. We conducted a research by formulated a needs analysis, designed, and implemented and tested a system. Needs analysis is done to collect the data needed in building the system. The design is planned which include architecture, database, and user interface design. Implementation studio system using Android 2.0, and programming languages PHP and Javascript. Results of tests performed show that SIG search locations in the city Bimbel institutions android-based field in accordance with the functional requirements of the system.